The quality of information literacy legislation secretariat of the regional people's representative council of East Java Province - Andre Fahreza; Tri Susantari (AKUNTABEL, 2022)
This study aims to describe the quality of information literacy legislation of DPRD members and staff of the DPRD Secretariat of East Java Province in the formation of regional regulations. The research method used is qualitative with a phenomenological approach, to understand phenomena through opinions, perceptions, behaviors, motivations, and experiences of research subjects. The subjects in this study were members of the DPRD and DPRD secretariat staff who were involved in the formation of regional regulations. There are nine resource persons for the council members, while the staff for the secretariat of the council are 14 people. Data collection techniques using interviews and Focus Group Discussion. The results of data collection grouped and arranged in descriptive narratives according to the research problem. This study finds that the DPRD secretariat and council members have worked collaboratively in the formulation of regional regulations. The conclusions of this study include, (1) the quality of information literacy for legislators and DPRD secretariat staff is quite reliable. (2) the capacity building programs to facilitate the legislative function can improve information literacy in legislation. (3) The source of literacy is Regional Regulation Number 13 of 2018 concerning the Establishment of Regional Legal Products (4) The secretariat library of the East Java Provincial DPRD acts as the main literacy room for council members and secretariat staff of the East Java Provincial DPRD.